Cardiac Magnetic Resonance Imaging - A Predictor Tool for Sudden Cardiac Death - Fatema, Nilufar; Siddique, Md Abu; Banerjee, Sajal Krishna; Ahsan, Syde Ali; Rahman, Fazlur; Ahmed, Chaudhury Meshkat; Muqeet, MA; Rahman, Mohammad Atiqur; Ahmed, Khurshed; Sharmin, Elora; et al. (University Heart Journal, 2011)
Cardiovascular magnetic resonance (CMR) detects myocardial fibrosis, which appears as late gadolinium enhancement (LGE) after gadolinium contrast administration and may convey prognostic importance. Myocardial fibrosis is the source of malignant arrhythmia like ventricular tachycardia or ventricular fibrillation. Sudden cardiac death occurs in these group patients. By detecting myocardial fibrosis we can select these groups of patients for implantable cardioverter defibrillator. Thus sudden cardiac death can be prevented in some extent. Keywords: Cardiac MRI; Sudden cardiac death. DOI: 10.3329/uhj.v6i2.7253 University Heart Journal Vol. 6, No. 2, July 2010 pp.90-92